Menanamkan budaya disiplin menabung dengan memanfaatkan celengan pada siswa kelas iii b di mi ddi tani aman loa janan ilir - Mariana Lamuda; Reni Ardiana (Institute of Computer Science (IOCS), 2023)
The culture of saving discipline is one way to accustom children to managing money, the benefits of saving can be obtained when carrying out this saving activity regularly and diligently. This aims to carry out a frugal lifestyle and is also a development characteristic not to generate money which should be implemented early on. This research aims to apply the discipline of saving by utilizing piggy banks in the learning process. The type of research carried out is Evaluative (summative evaluation). The research design used is qualitative. Understanding of how to manage personal finances wisely and according to needs. This financial education must be given from an early age to children, especially preschool and elementary school children. The goal is that introduction from childhood will help children get used to managing their money properly and correctly from childhood to adulthood and be able to make the right decisions in using their money. The population in the study were all class III B MI DDI Tani Aman students in the 2023/2024 academic year with a sample of 1 class with a total of 28 students. The results of this study indicate that the use of piggy banks in the learning process of saving a culture of saving among students, it can be concluded that the use of piggy banks has a significant effect on students' attitudes in setting aside their money for savings and learning to save life and value money from an early age.